Momentum in tennis matches at Grand Slam tournaments - O`Donoghue, P. (World Congress of Performance Analysis of Sport IX, 2012)
Previous investigations have provided evidence for and against the existence of momentum in sports performance (Bar Eli et al., 2006). Previous notational analysis research in tennis has failed to reveal more sequences of points of various lengths than would be expected by chance (O`Donoghue and Brown, 2009). However, the work of O`Donoghue and Brown was applied at the point level rather than at broader game and set levels. Analysing momentum in terms of games in tennis is problematic due to the dominance of the serve. Therefore, the purpose of the current investigation is analyse momentum at the set level in tennis. All completed matches of the 2009 to 2011 Grand Slam singles tournaments were included in the investigation. Winning players always win the last set of a match and if the preceding set outcomes are independent then a chi square goodness of fit test would not find a significant difference between the distribution of matches of different set orderings and an expected uniform distribution. Table 1 reveals that there is evidence momentum at the set level in men`s singles with eventual winning players having lost the first set of 4 set matches more than expected and eventual winning players having lost the first set or first 2 sets of 5 set matches more than expected. In women`s singles, the eventual winning player lost the first set more than significantly than expected at the French Open.